Clinical pharmacology and lesion penetrating properties of second- and third-line antituberculous agents used in the management of multidrug-resistant (MDR) and extensively-drug resistant (XDR) tuberculosis. - Dartois, Véronique (Curr Clin Pharmacol, 2010)
Failure of first-line chemotherapy to cure tuberculosis (TB) patients occurs, in part, because of the development of resistance to isoniazid (INH) and rifampicin (RIF) the two most sterilizing agents in the four-drug regimen used to treat primary infections. Strains resistant to both INH and RIF are termed multidrug-resistant (MDR). Treatment options for MDR patients involve a complex array of twenty different drugs only two classes of which are considered to be highly effective (fluoroquinolones and aminoglycosides). Resistance to these two classes results in strains known as extensively drug-resistant (XDR) and these types of infections are becoming increasingly common. Many of the remaining agents have poorly defined pharmacology but nonetheless are widely used in the treatment of this disease. Several of these agents are known to have highly variable exposures in healthy volunteers and little is known in the patients in which they must be used. Therapeutic drug monitoring (TDM) is infrequently used in the management of MDR or XDR disease yet the clinical pharmacokinetic studies that have been done suggest this might have a large impact on disease outcome. We review what is known about the pharmacologic properties of each of the major classes of second- and third-line antituberculosis agents and suggest where judicious use of TDM would have the maximum possible impact. We summarize the state of knowledge of drug-drug interactions (DDI) in these classes of agents and those that are currently in clinical trials. Finally we consider what little is known about the ability of TB drugs to reach their ultimate site of action - the interior of a granuloma by penetrating the diseased lung area. Careful consideration of the pharmacology of these agents is essential if we are to avoid further fueling the growing epidemic of highly drug-resistant TB and critical in the development of new antituberculosis drugs.